Collapsing the modal collapse argument: On an invalid argument against divine simplicity. (31st July 2018) - Tomaszewski, Christopher
Abstract: One of the most pressing objections against Divine simplicity is that it entails what is commonly termed a 'modal collapse', wherein all contingency is eliminated and every true proposition is rendered necessarily true. In this paper, I show that a common form of this argument is in fact famously invalid and examine three ways in which the opponent of Divine simplicity might try to repair the argument. I conclude that there is no clear way of repairing the argument that does not beg the question against the doctrine of Divine simplicity.